Increasing Students’ Reading Comprehension Of Report Text Through The Use Of Problem Posing Method At Muhammadiyah Junior High School - admin; Jasuli Jasuli (Universitas Muhammadiyah Gresik, 2017)
This study attempts to describe how the students achieve reading ability progress using the Problem Posing Method (henceforth PPM). Based on the early observation stage, it is found that subjects to this study tended be difficult comprehending English texts particularly report text. The PPM was opted to renew the teaching method in the class since it emphasized that learning should be started by knowledge, experience, and then related to real concept. To solve the problems, Classroom Action Research (henceforth CAR) design by Kemmis and McTaggart (1998) was done, consisting of planning, acting, observing and reflecting. The third year students at SMP Muhammadiyah 6 Malang consisting of twelve students are subject to this study. While the instruments of the study covered observation and test. The results of this study found that students’ difficulty in reading report text could be drastically reduced within one cycle to meet the criteria of success.